Pengaruh Live Streaming Video dan Shopping Enjoyment terhadap Impulse Buying Behavior - Tantri; Oktini, Dede R. (UNISBA Press, 2024)
Abstract. The phenomenon of online shopping through marketplaces makes the buying and selling process easier in the community. Lazada, which is one of the B2C e-commerce, provides a variety of products and marketplace features that connect sellers with buyers in real time, namely by providing a video live streaming feature. However, the ease and comfort of online transactions not only has a positive impact, but also has a negative impact in the form of impulsive purchasing behavior. Therefore, this study aims to determine the influence of Live Streaming Video and Shopping Enjoyment on Impulse Buying Behavior on Lazada marketplace users in the city of Bogor. Types of research include descriptive and verifiable research with quantitative methods. The sampling technique used is purposive sampling, with data collection through a survey method using a questionnaire instrument. The object of this research is active users of the Lazada marketplace in the city of Bogor with a sample of 100 respondents. Data analysis using SPSS software program tool version 25. Validity tests and reliability tests are carried out to ensure the accuracy and consistency of the research instruments. Classical assumption tests are performed to ensure data quality. The results of the analysis show that live streaming video and shopping enjoyment partially and simultaneously have a significant influence on impulse buying behavior. This is evidenced by the results of Fcal being greater than Ftabel (15,349 > 3,090). Abstrak. Fenomena belanja online melalui marketplace mempermudah proses jual beli di masyarakat. Lazada yang merupakan salah satu e-commerce B2C menyediakan beragam produk dan fitur marketplace yang menghubungkan penjual dengan pembeli secara real time, yaitu dengan menyediakan fitur live streaming video. Namun, kemudahan dan kenyamanan transaksi online tersebut tidak hanya berdampak positif, tetapi juga berdampak negatif dalam bentuk perilaku pembelian masyarakat yang impulsif. Maka dari itu, penelitian ini bertujuan untuk mengetahui pengaruh Live Streaming Video dan Shopping Enjoyment terhadap Impulse Buying Behavior pada pengguna marketplace Lazada di kota Bogor. Jenis penelitian termasuk penelitian deskriptif dan verifikatif dengan metode kuantitatif. Teknik sampling yang digunakan adalah purposive sampling, dengan pengumpulan data melalui metode survei menggunakan instrumen kuesioner. Objek penelitian ini adalah pengguna aktif marketplace Lazada di kota Bogor dengan jumlah sampel sebanyak 100 responden. Analisis data menggunakan alat bantu program software SPSS versi 25. Uji validitas dan uji reliabilitas dilakukan untuk memastikan ketepatan dan konsistensi instrumen penelitian. Uji asumsi klasik dilakukan untuk memastikan kualitas data. Hasil analisis menunjukkan bahwa live streaming video dan shopping enjoyment secara parsial dan simultan memiliki pengaruh yang signifikan terhadap impulse buying behavior. Hal ini dibuktikan dari hasil Fhitung lebih besar dari Ftabel (15,349 3,090).